Civil society anti-corruption efforts the case of the millennium challenge corporation's engagement in Ukraine - Grossmann, Juhani (2010)
The recently established new role of civil society in development assistance issued through the United States Millenium Challenge Corporation (MCC) can be seen in the MCC approach to development aid, especially its indicator-driven innovations in the general context of development assistance. Three types of civil society organization engagements are reviewed: indicator creation, in-country project design and implementation, and board membership and ongoing consultation. Finally, a conclusion about the degree of interaction and its effectiveness to date is made.
Keywords: Governance; Millennium Challenge Corporation (US); Civil society; Foreign aid (American)